Magnetic catalyst and its preparation method and application
By using a magnetic catalyst composed of magnetic support and nickel in a magnetic stable bed, the dialdehyde conversion rate and difficulty in removing by-products in the prior art are solved, and high-purity diamine is achieved Preparation and recycling of catalysts have promoted the domestic production of polyamide fields.
Patent Information
- Application Number
- CN202211729430.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The use of high-load catalysts in the existing diamine synthesis process leads to low conversion of dialdehydes, difficult to remove by-products, affecting product performance, and insufficient domestic production of diamine technology, limiting the development of the polyamide field.
Using a magnetic catalyst composed of magnetic support and nickel, the dialdehyde reduction amination reaction is carried out in a magnetic stable bed, and the magnetic separation characteristics of the magnetic catalyst are used for catalysis, which avoids the generation of by-products in the alcohol solvent environment and achieves high purity. amine preparation and facilitate the recycling and reuse of catalysts.
The preparation of high-purity diamines is achieved, the generation of by-products is avoided, the purity of diamines and the regeneration ability of catalysts is improved, and the domestic production needs in the field of polyamides are met.
Smart Images

Figure CN115920903B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a magnetic catalyst and a preparation method and application thereof. Background Art
[0002] Aliphatic diamines, as important chemical raw materials, play an irreplaceable role in the synthesis of polymer materials such as polyester and polyamide. According to the data from the Sustainable Textile Promotion Association, the global polyamide production in 2020 was 5.4 million tons. Polyamide is widely used in electronic appliances, automotive industry, equipment manufacturing and other fields. The vast market space for polyamide has led to an increasing demand for material monomer diamines. However, most of these diamine monomers are produced by chemical synthesis, and the core technology has long been monopolized by foreign companies. The relevant diamine monomer synthesis technology has become a bottleneck process for related polymer materials in my country. Therefore, the localization of diamine technology is of vital importance to promoting the development of my country's polymer materials, especially polyamide.
[0003] Reductive amination of the corresponding dialdehyde is one of the methods for preparing related diamines. The production of nonanediamine is mainly produced by reductive amination of nonanedialdehyde. Kuraray Company first determined its industrial production method in the world through reductive amination reaction. In the existing process, when using reductive amination to produce diamines, most of them use high-load nickel or Raney nickel as a catalyst in the reactor. In this way, when using water solvent, the conversion rate of dialdehyde is not high and the yield is low; when using alcohol solvent, a small amount of alcohol will be reduced to produce amine. When the alcohol solvent is recycled, the generated amine will gradually accumulate and react with dialdehyde to generate by-products that are difficult to remove. For example, methanol is used as a solvent in CN1446793A. Although the yield of diamine can reach 93%, the hydroxyl group of methanol will be reductively aminated to methylamine, and methylamine will react with the dialdehyde in the raw material to generate diamine in which the hydrogen atom in the amino group is replaced by methyl, generating N-methyl substituted diamine, and the performance of N-methyl substituted diamine is similar to that of diamine, and it is difficult to remove by processes such as distillation, thus becoming an impurity of diamine. When the obtained diamine is used as a polymer or chemical raw material, it will affect the product performance. Summary of the invention
[0004] The present invention provides a magnetic catalyst and a preparation method and application thereof. The catalyst provided by the present invention is placed in a magnetically stabilized bed and applied in catalyzing the reductive amination reaction of dialdehydes, which can not only produce high-purity diamine monomers but also facilitate the recovery and reuse of the catalyst.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a magnetic catalyst, which is composed of a magnetic carrier and nickel; the magnetic carrier is composed of a coating layer covering a magnetic center; the magnetic center is iron oxide or cobalt oxide; the coating layer is aluminum oxide, silicon oxide or zinc oxide.
[0006] Preferably, in terms of weight percentage, the coating layer accounts for 50-95% of the magnetic carrier, the magnetic center accounts for 5-50% of the magnetic carrier, and the nickel accounts for 20-45% of the magnetic catalyst.
[0007] Preferably, the particle size of the magnetic catalyst is in the range of 10 to 25 μm; the specific saturation magnetization Ms of the magnetic catalyst is in the range of 5 to 10 emu·g -1 ; The residual magnetization Mr is 0.3~1emu·g -1 .
[0008] The present invention provides a method for preparing the magnetic catalyst described in any one of the above, comprising the following steps:
[0009] 1) adding an alkaline solution dropwise to a cobalt salt solution or an iron salt solution to react and obtain a hydroxide suspension;
[0010] 2) adjusting the pH of the hydroxide suspension to 9-11, and after the adjustment, adding 1-10 mol / L of aluminum salt solution, zinc salt solution or ethyl orthosilicate ethanol solution, aging, washing to neutrality, drying, grinding and roasting to obtain a magnetic carrier;
[0011] 3) impregnating the nickel nitrate solution on the magnetic carrier, drying, calcining and reducing the solution to obtain a magnetic catalyst.
[0012] Preferably, in step 2), the drying temperature is 60-100° C., the calcination temperature is 600-800° C., and the calcination time is 8-12 hours.
[0013] Preferably, in step 3), the drying temperature is 60-100° C., the calcination temperature is 300-500° C., and the calcination time is 4-6 hours.
[0014] The present invention provides use of any one of the magnetic catalysts described above in catalyzing the reductive amination reaction of dialdehydes.
[0015] Preferably, the reductive amination reaction of the dialdehyde is carried out in a magnetically stabilized bed, a magnetic catalyst is placed in the magnetically stabilized bed, and then a mixer of hydrogen and ammonia and dialdehyde substances are respectively introduced into the magnetically stabilized bed for reaction.
[0016] Preferably, the dialdehyde substance is heated before being introduced into the magnetically stabilized bed; the heating temperature is 200-300°C.
[0017] Preferably, the control system pressure is 0.5-5 MPa, the mass flow rate of hydrogen is 10-200 mL / min, the mass flow rate of ammonia is 10-200 mL / min, the molar ratio of hydrogen to amine is 1 / 1, the molar ratio of hydrogen to dialdehyde substances is 30-60:1, the space velocity is 0.5-5 / h, and the magnetic field strength is 5-150 kA / m.
[0018] Compared with the prior art, the advantages and positive effects of the present invention are:
[0019] The invention provides a magnetic catalyst, which is a magnetic catalyst powder composed of a magnetic carrier and nickel, and a magnetically stabilized bed reduction amination process is developed using the catalyst. When the catalyst presents a chain-like form in the magnetically stabilized bed, the bed layer has a stable structure of a fixed bed and has a certain fluidity. At the same time, the catalyst has the characteristics of magnetic separation, which is conducive to the recovery and regeneration of the catalyst. The magnetically stabilized bed reduction amination process developed using the catalyst can be separated from the liquid environment of alcohol, avoids the generation of by-products that are difficult to remove, and can produce high-purity diamine monomers. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a magnetically stabilized bed experimental device provided by the present invention;
[0021] Among them, 1-stop valve; 2-liquid flow meter; 3-magnetic field coil; 4-material flow direction; 5-sensor; 6-test instrument; 7-computer; 8-distributor; 9-gas inlet; 10-gas compressor; 11-liquid storage tank with heater; 12-gas flow meter. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The invention provides a magnetic catalyst, which consists of a magnetic carrier and nickel; the magnetic carrier consists of a coating layer covering a magnetic center; the magnetic center is iron oxide or cobalt oxide; the coating layer is aluminum oxide, silicon oxide or zinc oxide.
[0024] The magnetic catalyst provided by the present invention is preferably 50-95% of the magnetic carrier in terms of weight percentage, and the magnetic center is preferably 5-50% of the magnetic carrier. The nickel is 20-45% of the catalyst. In the present invention, a layer of spinel structure is formed between the magnetic center and the coating layer. Under the above-defined range of the content of the magnetic carrier and the coating layer, the spinel structure is located exactly between the magnetic center and the coating layer. If there are too many magnetic centers, the spinel structure can be detected in the coating layer. In this state, after the active substance is loaded, the catalyst activity is low; if there are too many coating layers, the spinel structure is detected in the magnetic center, the catalyst magnetization intensity is low, and the use requirements of the magnetic stabilized bed cannot be met. For example, when iron and aluminum are calcined at a high temperature of 600-800 degrees Celsius, when the iron oxide comes into contact with the aluminum oxide, the two will form an aluminum-iron spinel structure. If the ratio is properly adjusted, when the iron in the magnetic center and the aluminum oxide in the coating form a stable spinel structure between the two, it will prevent the two from further reacting, thereby forming a stable carrier structure. If the iron content is low, then the iron oxide in the magnetic center is low, and the magnetic center will inevitably have a spinel structure, affecting the magnetism. If the coating content is low, similarly, the spinel structure will be detected in the coating, affecting the loading of the active substance.
[0025] In the present invention, the particle size of the magnetic catalyst is preferably 10 to 25 μm. The specific saturation magnetization Ms of the magnetic catalyst is preferably 5 to 10 emu·g -1 ; The residual magnetization Mr is preferably 0.3 to 1emu·g -1 .
[0026] The present invention provides a method for preparing the magnetic catalyst described in any one of the above, comprising the following steps:
[0027] 1) adding an alkaline solution dropwise to a cobalt salt solution or an iron salt solution to react and obtain a hydroxide suspension;
[0028] 2) adjusting the pH of the hydroxide suspension to 9-11, and after the adjustment, adding 1-10 mol / L of aluminum salt solution, zinc salt solution or silicon salt solution, aging, washing to neutrality, drying, grinding and roasting to obtain a magnetic carrier;
[0029] 3) impregnating the nickel nitrate solution on the magnetic carrier, drying, calcining and reducing the solution to obtain a magnetic catalyst.
[0030] In the present invention, an alkaline substance solution is added dropwise to a cobalt salt solution or an iron salt solution to react to obtain a hydroxide suspension. In the present invention, the iron salt is preferably one or more of iron nitrate, iron sulfate and iron chloride; the cobalt salt is preferably one or more of cobalt nitrate, cobalt sulfate and cobalt chloride. The concentration of the cobalt salt solution or the iron salt solution is preferably 0.05 to 1 mol / L. In the present invention, the alkaline substance is preferably one or more of sodium hydroxide, potassium hydroxide and ammonia water. The concentration of the alkaline substance solution is preferably 1 to 10 mol / L. In the present invention, the molar ratio of the cobalt salt or iron salt to the alkaline substance is preferably 1:1 to 1:5.
[0031] After obtaining the hydroxide suspension, the present invention adjusts the pH of the hydroxide suspension to 9-11, and after the adjustment is completed, 1-10 mol / L of aluminum salt solution, zinc salt solution or ethyl orthosilicate ethanol solution is added dropwise, and after the addition is completed, aging, washing to neutrality, drying, grinding, and roasting are performed to obtain a magnetic carrier. In the present invention, the aluminum salt is preferably one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate; the zinc salt is preferably one or more of zinc chloride, zinc sulfate, and zinc nitrate. In the present invention, the aging time is preferably 2.5-3.5h. In the present invention, the drying temperature is preferably 60-100°C, the roasting temperature is preferably 600-800°C, and the roasting time is preferably 8-12h.
[0032] After obtaining the magnetic carrier, the present invention impregnates the nickel nitrate solution on the magnetic carrier, performs drying, roasting and reduction, and obtains a magnetic catalyst. In the present invention, the nickel nitrate solution is preferably a nickel nitrate solution with a mass fraction of 10% to 50%. In the present invention, the drying temperature is preferably 60 to 100°C, the roasting temperature is preferably 300 to 500°C, and the roasting time is preferably 4 to 6 hours. In the present invention, the reduction is preferably carried out in hydrogen at 100 to 500°C.
[0033] The method provided by the present invention first forms a precursor of the magnetic center, a metal hydroxide, and on this basis, produces a coating layer precursor in situ, and after calcination, a catalyst carrier with uniform particle size can be obtained. At the same time, this method has the advantages of being easy to adjust the size of the magnetic center and the thickness of the coating layer.
[0034] The present invention provides the use of any one of the above-mentioned magnetic catalysts in catalyzing the reductive amination reaction of dialdehydes. In the present invention, the dialdehyde is preferably 1,4-butanedialdehyde, 1,5-glutaraldehyde, 1,6-hexanedialdehyde, or 1,9-nonanedialdehyde; the target product of the reductive amination of the dialdehyde is 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, or 1,9-nonanediamine.
[0035] In the present invention, the reductive amination reaction of the dialdehyde is carried out in a magnetically stabilized bed. Specifically, a magnetic catalyst is placed in the magnetically stabilized bed, and then a mixer of hydrogen and ammonia and a dialdehyde substance are introduced into the magnetically stabilized bed for reaction. In the present invention, the specific structure of the magnetically stabilized bed is preferably as follows: Figure 1 described.
[0036] In the present invention, the dialdehyde substance is preferably heated before being introduced into the magnetically stabilized bed; the heating temperature is preferably 200-300°C. In the present invention, preferably, the control system pressure is 0.5-5MPa, the mass flow rate of hydrogen is 10-200mL / min, the mass flow rate of ammonia is 10-200mL / min, the hydrogen-amine molar ratio is 1 / 1, the molar ratio of hydrogen to dialdehyde substance is 30-60:1, the space velocity is 0.5-5 / h, and the magnetic field strength is 5-150kA / m. The catalytic reaction time of the reduction amination of dialdehyde is preferably 20-1000h.
[0037] The reductive amination reaction of dialdehyde is that aldehyde group is subjected to reductive amination reaction to generate amine under the action of hydrogen and ammonia, and the main side reaction is that aldehyde group and hydrogen generate hydroxyl group by reduction reaction (the side reaction of dialdehyde generating diamine is reflected in that one aldehyde group is reduced to form hydroxyl group, one becomes amine, or both aldehyde groups are reduced to hydroxyl group), and an important process condition of the selectivity of the reaction is the feed ratio of hydrogen and ammonia. Too much hydrogen or too little ammonia is easy to cause the side reaction method to generate, and too much ammonia, the corrosiveness of the gas is enhanced, and it is easy to etch the carrier of the catalyst, resulting in the collapse of the catalyst skeleton, the loss of active substances, the service life of the catalyst, the activity and selectivity will all decrease, and the catalyst cannot be used after regeneration. Under the above parameters defined in the present invention, the magnetic field strength and catalyst compatibility are good, the catalyst is arranged in a chain along the direction of the magnetic field line, and the bed is chain-shaped.
[0038] The present invention carries out the reduction amination reaction of dialdehyde in a magnetically stabilized bed. The use of the magnetically stabilized bed can not only avoid the solid particle loss phenomenon that often occurs in the fluidized bed operation, but also avoid the local hot spots that may occur in the fixed bed. At the same time, the effect of the external magnetic field effectively controls the interphase backmixing, and the uniform porosity makes it difficult for channel flow to occur inside the bed. Small solid particles will not cause excessive pressure drop, and the fluidity of the fine particles makes it very convenient to load and unload the solid.
[0039] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0040] Example 1
[0041] Take 200ml of 0.3mol / L ferric nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a brown ferric hydroxide suspension. After the reaction is completed, adjust the pH value to 10, and add 2000ml of 0.3mol / L aluminum sulfate solution while stirring, while keeping the solution pH value between 9-11. After the addition is completed, continue stirring for 3 hours for aging. Filter and wash until the pH value is between 7-8. Dry the filter cake in an oven at 60°C for 10 hours, grind the dried solid, and sieve it with 400 mesh. The sieved solid is roasted at 600°C for 10 hours in an air atmosphere using a muffle furnace. Magnetic carrier 1 is obtained, and the magnetic center of this magnetic carrier is ferric oxide and the coating layer is aluminum oxide. Referring to the national standard GB / T 9966.3-2020 Natural Stone Test Method, Part 3, the water absorption rate of the magnetic carrier was determined. The water absorption rate of the magnetic carrier was determined to be 130%.
[0042] Example 2
[0043] Take 200ml of 0.3mol / L ferric nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a brown ferric hydroxide suspension. After the reaction is completed, adjust the pH value to 11, and add 2000ml of 0.3mol / L ethyl orthosilicate ethanol solution while stirring, while keeping the solution pH value between 9-11. After the addition is completed, continue stirring for 3 hours for aging. Filter and wash until the pH value is between 7-8. The filter cake is dried in an oven at 60°C for 10 hours, and the dried solid is ground and sieved with 400 mesh. The sieved solid is roasted at 600°C for 10 hours in an air atmosphere using a muffle furnace. Magnetic carrier 2 is obtained, and the magnetic center of this magnetic carrier is ferric oxide and the coating layer is silicon dioxide.
[0044] Example 3
[0045] Take 200ml of 0.3mol / L ferric nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a brown ferric hydroxide suspension. After the reaction is completed, adjust the pH value to 11, and add 2000ml of 0.3mol / L zinc nitrate solution while stirring, while keeping the solution pH value between 9-11. Continue stirring for 3 hours after the addition is completed for aging. Filter and wash until the pH value is between 7-8. The filter cake is dried in an oven at 60°C for 10 hours, and the dried solid is ground and sieved with 400 mesh. The sieved solid is roasted at 600°C for 10 hours in an air atmosphere using a muffle furnace. Magnetic carrier 3 is obtained, and the magnetic center of this magnetic carrier is ferric oxide and the coating layer is zinc oxide.
[0046] Example 4
[0047] Take 200ml of 0.3mol / L cobalt nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a rose-red cobalt hydroxide suspension. After the reaction is completed, adjust the pH value to 11, and add 2000ml of 0.3mol / L aluminum sulfate solution while stirring, while keeping the solution pH value between 9-11. After the addition is completed, continue stirring for 3 hours for aging. Filter and wash until the pH value is between 7-8. Dry the filter cake in an oven at 60°C for 10 hours, grind the dried solid, and sieve it with 400 mesh. The sieved solid is roasted at 800°C for 8 hours in an air atmosphere using a muffle furnace. Magnetic carrier 4 is obtained, and the magnetic center of this magnetic carrier is cobalt tetroxide and the coating layer is aluminum oxide.
[0048] Example 5
[0049] Take 200ml of 0.3mol / L cobalt nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a rose-red cobalt hydroxide suspension. After the reaction is completed, adjust the pH value to 11, and add 2000ml of 0.3mol / L ethyl orthosilicate ethanol solution while stirring, while keeping the solution pH value between 9-11. After the addition is completed, continue stirring for 3 hours for aging. Filter and wash until the pH value is between 7-8. The filter cake is dried in an oven at 100°C for 8 hours, and the dried solid is ground and sieved with 400 mesh. The sieved solid is roasted at 600°C for 12 hours in an air atmosphere using a muffle furnace. Magnetic carrier 5 is obtained, and the magnetic center of this magnetic carrier is cobalt tetraoxide and the coating layer is silicon dioxide.
[0050] Example 6
[0051] Take 200ml of 0.3mol / L cobalt nitrate aqueous solution and place it in a beaker. Use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring. After the addition is completed, continue to react for 3 hours. At this time, it is a rose-red cobalt hydroxide suspension. After the reaction is completed, adjust the pH value to 11, and add 2000ml of 0.3mol / L zinc nitrate solution while stirring, while keeping the solution pH value between 9-11. Continue stirring for 3 hours after the addition is completed for aging. Filter and wash until the pH value is between 7-8. Dry the filter cake in an oven at 60°C for 10 hours, grind the dried solid, and sieve it with 400 mesh. The sieved solid is roasted at 600°C for 10 hours in an air atmosphere using a muffle furnace. Magnetic carrier 6 is obtained, and the magnetic center of this magnetic carrier is cobalt tetroxide and the coating layer is zinc oxide.
[0052] Example 7
[0053] According to the nickel loading amount of 30% by mass, nickel nitrate is impregnated on the magnetic carrier using the equal volume impregnation method. Take 18.7g of nickel nitrate, dissolve it in 26g of water, slowly add 20g of magnetic carrier 1 to the aqueous solution of nickel nitrate and stir continuously until the catalyst carrier completely absorbs the solution. Use an oven to dry at 60°C, after drying, roast at 400°C for 5 hours, and use a tubular furnace in a hydrogen atmosphere to reduce at 400°C to obtain catalyst A, the particle size of catalyst A is 10-25μm.
[0054] The same steps were followed, but different catalysts were obtained by replacing the magnetic carrier or changing the content of the active component. The results are as follows:
[0055] Table 1 Catalyst ingredients
[0056]
[0057]
[0058] Comparative Example 1
[0059] The difference from Example 7 is that the magnetic carrier 1 is directly used for the reductive amination reaction without adding active components.
[0060] Comparative Example 2
[0061] The difference from Example 7 is that the content of the active component is 10%.
[0062] Comparative Example 3
[0063] The difference from Example 7 is that the particle size of the catalyst ranges from 50 to 100 μm.
[0064] The preparation scheme is as follows: take 200ml of 0.3mol / L ferric nitrate aqueous solution and place it in a beaker, use a peristaltic pump to add 300mL of 1mol / L sodium hydroxide solution while stirring, and continue to react for 5 hours after the addition is completed. At this time, it is a brown ferric hydroxide suspension. After the reaction is completed, the pH value is adjusted to 10, and 2000ml of 0.3mol / L aluminum sulfate solution is added while stirring, while keeping the pH value of the solution between 9 and 11. After the addition is completed, continue stirring for 5 hours for aging. Filter and wash until the pH value is between 7 and 8. Dry the filter cake in an oven at 60°C for 10 hours, grind the dried solid, and sieve it with 200 mesh. The sieved solid is roasted at 600°C for 10 hours in an air atmosphere using a muffle furnace. Magnetic carrier 1 is obtained, and the magnetic center of this magnetic carrier is ferric oxide and the coating layer is aluminum oxide. The particle size of the carrier was increased by prolonging the generation time of iron hydroxide and aluminum hydroxide, and then the evaluation was performed after loading 30% of the active component using the conditions of Implementation 7.
[0065] Comparative Example 4
[0066] Catalyst A was used to react in an autoclave reactor. 20 g of catalyst A, 100 g of 1,9-nonanedialdehyde and 100 g of methanol were added to a 500 ml high-pressure reactor. The system was connected to a hydrogen-ammonia mixture with a molar ratio of hydrogen to ammonia of 1 / 1. The hydrogen-ammonia mixture was replaced three times. After the replacement, the gas pressure was maintained at 1 MPa, the reaction temperature was 180°C, and the reaction time was 3 hours.
[0067] Comparative Example 5
[0068] A commercial 50% nickel / diatomaceous earth catalyst was used to react in a kettle reactor. 20 g of 50% nickel / diatomaceous earth catalyst, 100 g of 1,9-nonanedialdehyde and 100 g of methanol as a solvent were added to a 500 ml high-pressure reactor. A hydrogen-ammonia mixture with a molar ratio of hydrogen to ammonia of 1 / 1 was connected to the system. The hydrogen-ammonia mixture was replaced three times. After the replacement, the gas pressure was maintained at 1 MPa, the reaction temperature was 180°C and the reaction time was 3 hours.
[0069] Comparative Example 6
[0070] The sample after reaction in Comparative Example 4 was filtered to recover the catalyst, and then treated with reduced pressure distillation to obtain methanol and 1,9-nonanediamine products. The recovered catalyst and methanol solution were continuously used, and the reaction times were 10 times in total.
[0071] Comparative Example 7
[0072] The sample after the reaction of Comparative Example 5 was filtered to recover the catalyst, and then treated with reduced pressure distillation to obtain methanol and 1,9-nonanediamine products. The recovered catalyst and methanol solution were continuously used, and the reaction times were 10 times in total.
[0073] Example 8
[0074] Add 20g of catalyst A prepared in the embodiment to the magnetically stabilized bed, add 1,4-butanedial to the liquid storage tank (the heating temperature of the liquid storage tank is 240°C), and connect hydrogen and ammonia at the gas inlet; the control system pressure is 1.5mPa, the mass flow rate of hydrogen is 50mL / min, the hydrogen-ammonia feed molar ratio is 1 / 1, the feed molar ratio of hydrogen to dialdehyde is 20 / 1, the control air velocity is 1.5 / h, the magnetic field strength is adjusted to 20kA / m, the catalyst is in a magnetically stable state, and the reduction amination catalyst of 1,4-butanedial reacts for 10 hours. Detection is performed using gas chromatography, and the reaction is 10 hours. The conversion rate of 1,4-butanedial is 99.2%, and the selectivity is 99.3%. After 100 hours of reaction, the conversion rate of 1,4-butanedial is 96.8%, and the selectivity is 97.6%. The activity and selectivity of the catalyst are well maintained. After 500 hours of reaction, the conversion rate of 1,4-butanedial drops to 80.4%, and the selectivity drops to 92.8%.
[0075] This catalyst was used to react 1,5-glutaraldehyde, 1,6-hexanedialdehyde, and 1,9-nonanedialdehyde. The reaction conditions and results are as follows:
[0076] Table 2 Reaction conditions and results of different aldehyde compounds
[0077]
[0078]
[0079] Catalyst A, which had reacted for 500 hours, was taken out from the magnetically stabilized bed, the surface of the catalyst was cleaned with ethanol, dried, placed in a tubular furnace, and calcined for 2 hours at 400°C in an air atmosphere. After the calcination, the atmosphere was changed to hydrogen, and the catalyst was reduced at 200°C for 1 hour to obtain the regenerated catalyst A.
[0080] The regenerated catalyst A was continued to be used to evaluate 1,4-butanedialdehyde under the above reaction conditions. After 10 hours of reaction, the conversion rate of 1,4-butanedialdehyde was 98.4% and the selectivity was 98.3%. It can be seen that after the catalyst was regenerated, its activity was restored to a certain extent. Although the activity is not as good as the first reaction, the difference is small and the effect is similar, indicating that the catalyst can be recycled and has a long service life.
[0081] Example 9
[0082] 1,9-nonanedialdehyde was evaluated using different catalysts. The heating temperature of the liquid storage tank was 240°C, the control system pressure was 1.5mPa, the mass flow rate of hydrogen was 50mL / min, the hydrogen-ammonia feed molar ratio was 1 / 1, the feed molar ratio of hydrogen to dialdehyde was 20 / 1, the control space velocity was 1.5 / h, the magnetic field strength was 20kA / m, and the reaction time was 10 hours. The conversion rate and selectivity were directly detected in the gas phase after the sample reaction was completed. The sample was purified by vacuum distillation before the sample purity test. The experimental results are shown in Table 3:
[0083] Table 3
[0084]
[0085]
[0086] As can be seen from Table 3, the magnetically stabilized bed catalyst provided by the present invention is evaluated for reduction amination reaction in a magnetically stabilized bed, and its catalytic activity is high, the selectivity is high, and the prepared diamine has high purity. Among them, the catalytic activity is the highest when ferric oxide is used as the magnetic center and aluminum oxide is used as the coating layer. The activity and selectivity are relatively low when zinc oxide is used as the coating layer. The main reason is that zinc oxide is easily etched by ammonia. One of the reasons why aluminum oxide has a better effect is that aluminum oxide can resist the etching of ammonia to a certain extent. Comparative Examples 4 and 5 are evaluations of homemade magnetically stabilized bed catalysts and traditional commercial catalysts in a reactor. It can be seen that the conversion rate and selectivity of the two in the reactor are close, and the catalyst activity is comparable to that of commercial catalysts. It can be seen from Comparative Examples 6 and 7 that after 10 reaction cycles, the conversion rate and selectivity of the two catalysts have a slight decrease. However, the purity has dropped to about 95%, and the main impurity is N-methyl substituted diamine according to gas phase detection.
[0087] Example 10
[0088] The methanol after the reaction of Comparative Examples 4, 5, 6 and 7 was subjected to gas phase detection to analyze the changes in the components in the methanol.
[0089] Table 4
[0090] Case Methylamine content in methanol Comparative Example 4 0.06% Comparative Example 5 0.09% Comparative Example 6 0.59% Comparative Example 7 0.65%
[0091] It can be seen from Table 4 that the methylamine content has been increasing during the methanol recycling process. Combined with the purity data of 1,9-nonanediamine in Table 3, it can be seen that the use of magnetic stabilization for reductive amination reaction is free from the limitation of using alcohol solution, avoids the production of difficult-to-separate N-methyl substituted diamine, and is easier to obtain diamine monomers with higher purity.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Use of a magnetic catalyst in catalyzing the reductive amination of dialdehydes to prepare diamines, characterized in that: The magnetic catalyst is composed of a magnetic carrier and nickel; the magnetic carrier is composed of a coating layer covering a magnetic center; the magnetic center is ferric oxide; the coating layer is aluminum oxide; by weight percentage, the coating layer is 50-95% of the magnetic carrier, the magnetic center is 5-50% of the magnetic carrier; the nickel is 20-45% of the magnetic catalyst; the particle size range of the magnetic catalyst is 10-25 μm; The method for preparing the magnetic catalyst comprises the following steps: 1) Adding an alkaline solution dropwise to an iron salt solution to react and obtain a hydroxide suspension; 2) adjusting the pH of the hydroxide suspension to 9-11, and after the adjustment, adding 1-10 mol / L aluminum salt solution dropwise, aging, washing to neutrality, drying, grinding, and roasting to obtain a magnetic carrier; the drying temperature is 60-100° C., the roasting temperature is 600-800° C., and the roasting time is 8-12 hours; 3) impregnating the nickel nitrate solution on the magnetic carrier, drying, calcining and reducing to obtain a magnetic catalyst; The reductive amination of dialdehyde to prepare diamine is carried out in a magnetically stabilized bed. A magnetic catalyst is placed in the magnetically stabilized bed, and then a mixed gas of hydrogen and ammonia and dialdehyde substances are respectively introduced into the magnetically stabilized bed for reaction.
2. The use according to claim 1, characterized in that: The specific saturation magnetization Ms of the magnetic catalyst is 5-10emu•g -1 ; The residual magnetization Mr is 0.3~1emu•g -1 .
3. The use according to claim 1, characterized in that: In step 3), the drying temperature is 60-100° C., the calcination temperature is 300-500° C., and the calcination time is 4-6 hours.
4. The use according to claim 1, characterized in that: The dialdehyde substance is heated before being introduced into the magnetically stabilized bed; the heating temperature is 200-300°C.
5. The use according to claim 4, characterized in that: The control system pressure is 0.5~5MPa, the hydrogen flow rate is 10~200mL / min, the ammonia flow rate is 10~200mL / min, the hydrogen-ammonia molar ratio is 1 / 1, the molar ratio of hydrogen to dialdehyde is 30~60:1, the space velocity is 0.5~5 / h, and the magnetic field strength is 5~150kA / m.
